1980
DOI: 10.1097/00004032-198004000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Radiation and Host Factors in Human Thyroid Tumors Following Thymus Irradiation

Abstract: NOMENCLATURE RR relative risk O/E observed to expected ratio z rate/ lo6 PY-rad standard deviate on the normal distribution excess tumors/106 personslyrlrad PY person-years at riskAbstract-In this paper thyroid tumor data from the 1971 survey of the Rochester, New York thymus irradiated population are further analyzed to study radiobiological and host factors. The analyses were based on the approx. 2650 irradiated subjects and 4800 sibling controls who had 5 or more years of follow-up. Twenty-four thyroid canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
1
1

Year Published

1981
1981
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 3 publications
2
35
1
1
Order By: Relevance
“…While, from this, the dog might appear to have a generally high sensitivity to radiation carcinogenesis, there is little question that this trend is most pronounced in dogs irradiated in the perinatal period, considering both the heightened responses in the young dogs and the greater degree of response throughout the life-span. The occurrence of thyroid neoplasia in our study, while not related to perinatal exposure, is consistent with the findings in humans which indicate that susceptibility to radiation induced thyroid cancer is greatest in early childhood (Shore et al (1985) )28)). In the dog, as in humans, both benign and malignant thyroid neoplasms resulted after radiation exposure.…”
Section: Discussionsupporting
confidence: 91%
“…While, from this, the dog might appear to have a generally high sensitivity to radiation carcinogenesis, there is little question that this trend is most pronounced in dogs irradiated in the perinatal period, considering both the heightened responses in the young dogs and the greater degree of response throughout the life-span. The occurrence of thyroid neoplasia in our study, while not related to perinatal exposure, is consistent with the findings in humans which indicate that susceptibility to radiation induced thyroid cancer is greatest in early childhood (Shore et al (1985) )28)). In the dog, as in humans, both benign and malignant thyroid neoplasms resulted after radiation exposure.…”
Section: Discussionsupporting
confidence: 91%
“…Ionizing radiation is a main well-established risk factor for thyroid cancer (Shore et al, 1985;Franceschi and Vecchia, 1994;Ron, 1995). For the general population, diagnostic radiology may be the main source of exposure to ionizing radiation, and an increased risk associated with diagnostic X-rays is also biologically plausible (Shore et al, 1985;Franceschi and Vecchia, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…For the general population, diagnostic radiology may be the main source of exposure to ionizing radiation, and an increased risk associated with diagnostic X-rays is also biologically plausible (Shore et al, 1985;Franceschi and Vecchia, 1994). Furthermore, the thyroid gland may be included in the radiation field when either the upper body or the chest is exposed to X-rays.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease of risk at higher doses is explained by the effect of cell killing (UNSCEAR 2006;Boice 2005). However, no leveling of TC risk was found by Shore et al (1985) at the doses of external radiation up to 10 Gy. In a case-control study following radiotherapy for childhood cancer, it was found that exposures around 60 Gy were associated with a high risk of TC (UNSCEAR 1994).…”
mentioning
confidence: 99%